2011
DOI: 10.1007/s10562-011-0570-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Esterification of Glycerol Catalysed by Tin Chloride (II): A Recyclable and Less Corrosive Process for Production of Bio-Additives

Abstract: In this work, a novel process based on use of a SnCl 2 Á2H 2 O catalyst which is less corrosive, inexpensive, and a water tolerant Lewis acid was employed for synthesis of fuel bio-additives from glycerol. High yields and selectivities were achieved for glycerol esterification with acetic acid under mild reaction conditions. The SnCl 2 catalyst showed to be as active as p-toluene sulfonic and sulfuric acid, catalysts commonly used in acid-catalysed esterification reactions. However, its use has significant adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 29 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…Further increase in temperature to 120 • C does not affect the triacetin selectivity. Similar findings have been reported by Goncalves et al [141] and Dosuna-Rodriguez et al [142]. However, contrary to the above, Rafi et al [125] revealed that increasing the temperature from 80 to 120 • C increased the glycerol conversion from 25 to 85%.…”
Section: Temperaturesupporting
confidence: 77%
“…Further increase in temperature to 120 • C does not affect the triacetin selectivity. Similar findings have been reported by Goncalves et al [141] and Dosuna-Rodriguez et al [142]. However, contrary to the above, Rafi et al [125] revealed that increasing the temperature from 80 to 120 • C increased the glycerol conversion from 25 to 85%.…”
Section: Temperaturesupporting
confidence: 77%
“…9 Triacetin plays simultaneously the roles of a solvent and an acyl donor in the synthesis of isoamyl acetate 10,11 catalyzed by lipase CALB or Amberlyst 36 and in the one-pot synthesis of cinnamyl acetate from cinnamaldehyde, 12 and only that of a reaction medium in the production of paclitaxel, 13 an anticancer drug. Due to the increasing interest in glycerol-derived esters, in the past few years great attention has been paid to glycerol acetylation with acetic acid (Scheme 1) and several studies have been published dealing with the use of solid acid catalysts, such as Amberlyst 15 or other sulphonic resins, [14][15][16][17] mesoporous materials with anchored sulphonic groups, 16,18,19 K10 montmorillonite, 17 SnCl 2 , 20 hydroxylated magnesium fluoride, 21 and heteropolyacids. 22,23 In general sulphonic solids, either resins or mesoporous materials, and K10 have shown much better performance than zeolites and other solid acids, such as niobic acid and sulphated zirconia.…”
Section: Introductionmentioning
confidence: 99%
“…206 On the other hand, organotin alkoxy is widely described in transesterication reactions. 207,208 Another widely generated organometallic complexes in the globe are organotin compounds. 209 They are used as catalysts in a variety of industrial processes in which esters are produced via (trans)esterication, such as the synthesis of fatty acid alkyl esters (FAAEs), 210 polyesters 211,212 and lactones.…”
Section: Organometallic Catalysismentioning
confidence: 99%